2017
DOI: 10.1182/blood-2016-05-672196
|View full text |Cite
|
Sign up to set email alerts
|

Interim PET-driven strategy in de novo diffuse large B-cell lymphoma: do we trust the driver?

Abstract: 18F-Fluorodeoxyglucose–positron emission tomography (FDG-PET) has become a central tool for both accurate initial staging and determination of prognosis after treatment of diffuse large B-cell lymphoma (DLBCL). However, the role of PET during treatment (iPET) in daily practice remains a matter of significant debate. This perspective reviews the published studies on iPET in DLBCL, including the methods used to analyze iPET, its timing, and studies of iPET-driven therapy to illuminate where daily practice may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
0
26
1
Order By: Relevance
“…Diffuse large B‐cell lymphoma (DLBCL) is the most prevalent type of non‐Hodgkin lymphoma. Although the addition of rituximab to a CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone)‐like regimen (R‐CHOP) has improved DLBCL outcomes significantly, over 25% of patients treated with R‐CHOP unfortunately experience treatment failure . The early recognition of patients with a poor prognosis and the tailoring of their curative remediation plan are undoubtedly key interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse large B‐cell lymphoma (DLBCL) is the most prevalent type of non‐Hodgkin lymphoma. Although the addition of rituximab to a CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone)‐like regimen (R‐CHOP) has improved DLBCL outcomes significantly, over 25% of patients treated with R‐CHOP unfortunately experience treatment failure . The early recognition of patients with a poor prognosis and the tailoring of their curative remediation plan are undoubtedly key interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the addition of rituximab to a CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone)-like regimen (R-CHOP) has improved DLBCL outcomes significantly, over 25% of patients treated with R-CHOP unfortunately experience treatment failure. 1 The early recognition of patients with a poor prognosis and the tailoring of their curative remediation plan are undoubtedly key interventions. For the past 20 years, the International Prognostic Index (IPI) has been the basis for initial risk stratification for patients with CHOP-treated DLBCL, facilitating treatment selection and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, in DLBCL, PET predicts response, but more intensive chemotherapy has failed to improve outcomes for patients with iPET+ scans [8,9]. Several large prospective studies such as the PETAL and LYSA trials demonstrated that treatment intensification such as the Burkitt-type approach or autologous stem cell transplantation fail to prevent iPET+ patients from having a higher risk of relapse than iPETpatients [10]. RCHOP-like chemotherapies have been proven to be effective in DLBCL for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Varied timing of iPET/CT has been reported in the literature, and in most studies, iPET/CT was performed after two or four cycles of chemotherapy . Tumor glucose metabolism in the early stage of disease has been recognized as a favorable prognostic factor in DLBCL regardless of the times at which iPET is performed …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Tumor glucose metabolism in the early stage of disease has been recognized as a favorable prognostic factor in DLBCL regardless of the times at which iPET is performed. 8 Determining the best method to interpret iPET is also a significant challenge. Although Deauville 5-point scale (DS) was recommended as a standard method, the variable positive predictive value (PPV) of iPET using visual analysis is a main point of contention.…”
Section: Introductionmentioning
confidence: 99%